Somitic mesoderm morphogenesis is necessary for neural tube closure during Xenopus development - Christodoulou, Neophytos; Skourides, Paris A. (Frontiers in Cell and Developmental Biology, 2023)
Neural tube closure is a fundamental process during vertebrate embryogenesis, which leads to the formation of the central nervous system. Defective neural tube closure leads to neural tube defects which are some of the most common human birth defects. While the intrinsic morphogenetic events shaping the neuroepithelium have been studied extensively, how tissues mechanically coupled with the neural plate influence neural tube closure remains poorly understood. Here, using Xenopus laevis embryos, live imaging in combination with loss of function experiments and morphometric analysis of fixed samples we explore the reciprocal mechanical communication between the neural plate and the somitic mesoderm and its impact on tissue morphogenesis. We show that although somitic mesoderm convergent extension occurs independently from neural plate morphogenesis neural tube closure depends on somitic mesoderm morphogenesis. Specifically, impaired somitic mesoderm remodelling results in defective apical constriction within the neuroepithelium and failure of neural tube closure. Last, our data reveal that mild abnormalities in somitic mesoderm and neural plate morphogenesis have a synergistic effect during neurulation, leading to severe neural tube closure defects. Overall, our data reveal that defective morphogenesis of tissues mechanically coupled with the neural plate can not only drastically exacerbate mild neural tube defects that may arise from abnormalities within the neural tissue but can also elicit neural tube defects even when the neural plate is itself free of inherent defects.